Pembangunan Hukum Hak Asasi Manusia di Indonesia dalam Era Globalisasi - Tami Rusli (Universitas Bandar Lampung (UBL), 2011)
This study is about development of human rights regulations in Indonesia inglobalization era. Perspective of law science, the revolution theory which until nowbecomes concern in Indonesian case, it is because there are lot of legal regulationswhich touch the lives of the basic welfare of the majority are still dominated by therule of law derived from colonial product, such as the Criminal Code, Civil Code andthe Commercial Code. Those legal regulations still have clash in substance with theconcept of human rights in Indonesia. This situation must have been realized, andthe awareness increases enthusiasm for the construction of national law. Should webuild a legal system based on Pancasila, ideas such as this gives a large place toexplore the principles of customary law in making laws to conform with the ideals ofthe law of Indonesia, namely willing the Pancasila and 1945 Constitution in whichthere is recognition of basic human rights as the realization of human rights.